PENGARUH KNOWLEDGE SHARING, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA SWARI SPA RELAXATION, BADUNG, BALI - Cokorda Prabu Pemayun; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
Along with advances in science and technology, every company is required to innovate continuously and have human resources with a high level of performance, so that they can have high competitiveness against other companies. This also applies to Swari Spa Relaxation. This research aims to analyze the influence of knowledge sharing, work environment, and compensation on employee performance at Swari Spa Relaxation, Badung. The number of samples used in this research was 46 people using the saturated sample method. Data collection uses a questionnaire. The data analysis technique uses multiple linear regression analysis. Hypothesis testing uses the F test and t test. The research results show that knowledge sharing has a positive and significant effect on employee performance at Swari Spa Relaxation, Badung. The work environment has a positive and significant effect on employee performance at Swari Spa Relaxation, Badung. Compensation has a positive and significant effect on employee performance at Swari Spa Relaxation, Badung. The limitation of this research is that this research only focuses on 3 variables, namely knowledge sharing, work environment, and compensation, while there are still many other variables which are thought to have an influence on employee performance.